Fear of cancer recurrence in lymphoma survivors: A descriptive study. Issue 3 (3rd May 2020) - Latella, Lauren E.; Rogers, Madeline; Leventhal, Howard; Parker, Patricia A.; Horwitz, Steven; Matasar, Matthew J.; Bylund, Carma L.; Kissane, David W.; Franco, Kara; Banerjee, Smita C.
Abstract: Objectives: Fear of cancer recurrence (FCR) is a common experience among cancer survivors and often persists after the termination of cancer treatments. The purpose of this paper was to evaluate FCR in survivors of Hodgkin's and diffuse large B-cell lymphomas, given a high rate of survivorship in this patient population. Research Approach: The parent study was a multi-site, cluster-randomized trial to assess a communication skills intervention: survivorship planning consultation (versus a time-attention control - wellness rehabilitation intervention) to promote transition to survivorship. Participants & Methodological Approach: 199 patients enrolled in the study and completed a survivorship (or control) consultation one-month after receiving the news of their survivorship status; 141 of those patients ( n  = 92 experimental arm, n  = 49 control arm) completed an interview at their 6-month follow-up consultation. In the interview, participants described frequency of FCR, causes of FCR, coping mechanisms, and specific things oncologists said to reduce FCR. Both qualitative and quantitative methods were utilized for analyzing participant responses. Findings: The majority (88%) of participants reported experiencing FCR, with a higher number of participants in the experimental arm significantly more likely to endorse FCR compared to the control group participants. The main causes of FCR were having medical appointments and concerns about potential relapse and secondary cancers. Participants endorsed utilizing self-sufficient coping mechanisms. As well, participants reported that oncologists most frequently cited specific cure rates of lymphoma to reduce patients' FCR. Interpretation & Implications for Psychosocial Providers: Communication skills training programs should emphasize FCR in survivorship consultations.